FORMATION OF COMPOSITE GLOBAL COMMODITY PRICES AS AN INFLATION INDICATOR FOR EAST JAVA - Anisha Wirasti Cahyaningrum (East Java Economic Journal, 2018)
With the average contribution of imports to Gross Regional Domestic Product (GRDP) in the last five years reaching 19.1%, the dynamics of global commodity prices also influence the economic performance of East Java, including the movement of inflation. A composite indicator of global commodity prices is needed to find out the impact of changes in various global commodity prices on inflation in East Java. By adopting the Bank Indonesia methodology in forming a composite global price known as the Imported Inflation Price Index (IHIM) which has considered the method of forming a global composite price created by the IMF (IMF Commodity Price Index), the compilation of East Java global price composites also examines the accuracy of commodity selection and aspects of data availability. The selected global price composite for East Java is a composite of seven global commodities which include food (wheat, soybeans, corn and CPO) and non-food (iron, gold and oil). These are two aspects determining the relative weight, namely (I) the import portion of the total input based on the Input-Output table and (ii) the commodity weight of derivatives in the East Java Consumer Price Index (IHK) basket. Furthermore, with OLS regression, the composite of East Java global commodity prices affects the core-traded inflation movement in East Java. Thus, the composite of global commodity prices in East Java can be used as an indicator of East Java inflation projections, especially core-traded inflation. This study, in general, will also examine the effect of the exchange rate impact on the movement of core inflation, especially traded groups in East Java. Based on the regression results it is known that the impact of the exchange rate movement on core traded inflation in East Java is more significant than the effect of world commodity price movements.